Social Media, Terrorist Content Prohibitions and the Rule of Law - Stuart Macdonald (George Washington University, 2019)
The importance of the rule of law to an effective counterterrorism strategy is widely accepted. Adherence to rule of law values protects both the legitimacy and moral authority of counterterrorism policies and legislation. This paper focuses on tech companies' prohibitions on terrorism-promoting content and evaluates these from the perspective of two specific rule of law values: minimalism and certainty. Drawing on the debates that have surrounded that UK's 'Encouragement of Terrorism' offence, the paper asks two questions. First, do the tech companies' prohibitions encompass indirect, as well as direct, encouragement? And, second, for the prohibitions to apply, must the encouragement of terrorism have been the purpose and/or the likely effect of the relevant content? The answer to neither question is clear from the wording of the prohibitions themselves. The paper argues that, in terms of the values of minimalism and certainty, it is important that the answers to both questions are made explicit. It also suggests how both questions should be answered and provides a proposed reformulation of the companies’ prohibitions on terrorism-promoting content.